Health Education Media â€œSmart with Your Foodsâ€ Increasing Selection of Foods Knowledge for Elementary School Students - Patriasih, Rita (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2017)
The importance of the application of healthy behaviors in elementary schools need serious attention. Results of a preliminary study revealed the low student behavior, especially on the selection of healthy foods. Efforts to do one of them by conveying this information by using the right media health education. This study aimed to increase the knowledge of elementary school students through health education media